Effectiveness Of Movement-Based Relaxation And Positive Affirmation Therapy in Reducing Anxiety And Pain Among Cancer Patients: A Quasi-Experimental Study - Candra, Muhamad Candra Romadon; Rochmawati, Erna (Journal of Applied Nursing and Health, 2026)
Background: Cancer patients frequently experience anxiety and pain that may negatively affect treatment adherence and quality of life. Complementary non-pharmacological interventions integrating relaxation, physical movement, and positive affirmation have shown potential benefits in symptom management. However, most previous studies evaluated relaxation, movement, or affirmation separately, and evidence regarding integrated mind–body interventions remains limited. This study aimed to examine the effectiveness of movement-based relaxation and positive affirmation therapy in reducing anxiety and pain among cancer patients. Methods: A quasi-experimental pretest–posttest control group design was conducted in an oncology inpatient unit of a tertiary hospital in Indonesia. This study adhered to the TREND guideline. The independent variable was movement-based relaxation combined with positive affirmation therapy, while the dependent variables were anxiety and pain levels. Forty-eight adult cancer patients were recruited using consecutive sampling and allocated into intervention (n = 24) and control groups (n = 24). The intervention group received six sessions (three times per week for two weeks; 25–30 minutes per session), while the control group received standard hospital care. Data were analyzed using the Wilcoxon Signed Rank Test and Mann–Whitney U Test. Results: Anxiety scores significantly decreased in the intervention group. Anxiety decreased from 61.3 ± 6.2 to 47.4 ± 7.1, and pain decreased from 6.9 ± 1.2 to 4.1 ± 0.9 in the intervention group. The mean difference in anxiety was 14.25 ± 5.18 (p < 0.001; 95% CI 11.82–16.68), while pain showed a mean difference of 2.67 ± 0.98 (p < 0.001; 95% CI 2.18–3.16), compared to the control group. Large effect sizes were observed for anxiety (d = 2.68) and pain (d = 2.54). Conclusion: Movement-based relaxation and positive affirmation therapy effectively reduced anxiety and pain among cancer patients. This integrated mind–body intervention represents a feasible complementary nursing strategy to enhance holistic oncology care.